2021
DOI: 10.3390/cells10071621
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Properties of NK Cells in Cancer and Other Angiogenesis-Dependent Diseases

Abstract: The pathogenesis of many serious diseases, including cancer, is closely related to disturbances in the angiogenesis process. Angiogenesis is essential for the progression of tumor growth and metastasis. The tumor microenvironment (TME) has immunosuppressive properties, which contribute to tumor expansion and angiogenesis. Similarly, the uterine microenvironment (UME) exerts a tolerogenic (immunosuppressive) and proangiogenic effect on its cells, promoting implantation and development of the embryo and placenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 213 publications
(322 reference statements)
0
19
0
Order By: Relevance
“…CD56 bright CD16 − cells have also been identified as the predominant tumor subset of NK cells in lung cancer [ 39 ]. The major factors contributing to peripheral blood NK-cell phenotype remodeling are TGF-β, glycodelin-A (GdA), prostaglandin E2 (PGE2), and hypoxia [ 40 ]. Our results showed that hypoxic lung cancer-derived EVs increased the polarization of NK cells to dNK-like cells with pro-angiogenic phenotypes, which have the ability to support angiogenesis in vitro with several soluble factors including, VEGF, CXCL1/2 and IL-8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD56 bright CD16 − cells have also been identified as the predominant tumor subset of NK cells in lung cancer [ 39 ]. The major factors contributing to peripheral blood NK-cell phenotype remodeling are TGF-β, glycodelin-A (GdA), prostaglandin E2 (PGE2), and hypoxia [ 40 ]. Our results showed that hypoxic lung cancer-derived EVs increased the polarization of NK cells to dNK-like cells with pro-angiogenic phenotypes, which have the ability to support angiogenesis in vitro with several soluble factors including, VEGF, CXCL1/2 and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore use the term “EVs” in the current report. Indeed, a variety of isolation methods based on different principles, such as ultracentrifugation, density gradient, precipitation, immune precipitation, membrane affinity, size-exclusion chromatography, iodixanol gradient and phosphatidylserine affinity, are available [ 40 , 57 ]. Different isolation methods yielded EVs with different profiles in terms of morphology, particle size, and content.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating NK cytotoxicity might be regulated by other factors, such as other surface receptors (NKp44, NKG2A, ITAM-KIR, etc. ), the production of IFN-g and TNF-a, NK cell maturation and development, proangiogenic features of NK cells, or the interaction with other immune cells such as regulatory T cells (34)(35)(36)(37)(38). It is worth noting that, although PBMC cytotoxicity is used to represent NK cytotoxicity in many studies, peripheral T cells might also exhibit cytotoxicity via the production of cytokines, such as IFN-g, TNF-a, and the human cytotoxic factor (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Antigens are the most frequent neurotransmitter medicines, while receptor tyrosine kinase agents are the most common direct amplifiers of VEGF activity. Curcumin inhibited VEGF and angiopoietin 1 and 2 gene production in EAT cells, VEGF and angiopoietin one oxidative stress in NIH3T3 cells, and KDR gene expression in HUVEC cells in a time-dependent manner [ 96 ]. Curcumin shown to inhibit VEGF production in blood clotting via mechanisms such as TGF release, COX-2 hypertrophy, hydrogen peroxide discharge, conventional and aberrant EGFR, Src signaling, and abnormal NF-B signaling [ 97 ].…”
Section: Therapeutic Applications Of Nanocurcumin Over Curcuminmentioning
confidence: 99%